2019
DOI: 10.14639/0392-100x-2361
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene expression profiling suggests epithelial dysfunction in polypoid chronic rhinosinusitis

Abstract: SUMMARY Chronic rhinosinusitis (CRS) is a heterogeneous inflammatory disorder resulting from a complex gene-environment interaction. Although its aetiology remains elusive, numerous studies reported gene expression alterations of factors apparently implicated in all aspects of the inflammatory response. However, most investigations are limited, unconfirmed analyses of a single gene. Moreover, studies concerning multiple gene expression analyses, usually on inflammatory mediators (e.g. cytokines), sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This aspect is the inspiring concept underlying the recent "reboot approach" 24 . Moreover, this region, in addition to a different embryological origin, shows a morpho-histological structure that is not identical to that of the middle meatus 22,25 . She et al demonstrated that 66% of CRS patients with CRS show marked inflammation in the inferior turbinate, but that the inflammation is much more intense in maxillary sinus mucosa 20 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This aspect is the inspiring concept underlying the recent "reboot approach" 24 . Moreover, this region, in addition to a different embryological origin, shows a morpho-histological structure that is not identical to that of the middle meatus 22,25 . She et al demonstrated that 66% of CRS patients with CRS show marked inflammation in the inferior turbinate, but that the inflammation is much more intense in maxillary sinus mucosa 20 .…”
Section: Discussionmentioning
confidence: 87%
“…This aspect is the inspiring concept underlying the recent “reboot approach” 24 . Moreover, this region, in addition to a different embryological origin, shows a morpho-histological structure that is not identical to that of the middle meatus 22 , 25 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, the authors suggested that the mucosal epithelial barrier is compromised in the context of CRS disease, especially CRSwNP, and that loss of AQP5, which might act as a tight junction protein, plays a role in the development of mucosal edema and the pathophysiology of nasal polyp formation [ 57 ]. Another study comparing normal control and CRSwNP tissue also reported a decrease in AQP5 in tissues from CRSwNP patients [ 58 ]. The authors of this study concluded that loss of AQP5 caused impaired tight junction regulation of water transport and cell volume and failure to maintain epithelial water homeostasis, resulting in edema and polyp formation and production of thick secretions—typical features of CRSwNP.…”
Section: Relationship Between Aqps and The Nasal Respiratory Epithmentioning
confidence: 99%
“…Chronic rhinosinusitis with nasal polyposis (CRSwNP) is characterised by chronic inflammation of the nasal mucosa with an altered remodelling process, which affects extracellular matrix (ECM) formation and facilitates mechanical dysfunction and oedema formation 1 . The pathogenesis of CRSwNP is still not fully understood 2,3 ; however, its foundation is the aforementioned chronic inflammatory process, characterised by a major imbalance in immunomodulation which increases inflammatory cells (such as dendritic cells, eosinophils, and T helper cells) and decreases immunoregulatory cells (such as regulatory T cells), as well as an impaired immunomodulation of mesenchymal stem cells 4,5 . Studies on the mechanical forces involved in nasal polyp development have been conducted in an attempt to at least partly elucidate the pathophysiology of CRSwNP 1,6,7 .…”
Section: Introductionmentioning
confidence: 99%